2021
DOI: 10.1098/rstb.2020.0317
|View full text |Cite
|
Sign up to set email alerts
|

The origins of human cumulative culture: from the foraging niche to collective intelligence

Abstract: Various studies have investigated cognitive mechanisms underlying culture in humans and other great apes. However, the adaptive reasons for the evolution of uniquely sophisticated cumulative culture in our species remain unclear. We propose that the cultural capabilities of humans are the evolutionary result of a stepwise transition from the ape-like lifestyle of earlier hominins to the foraging niche still observed in extant hunter–gatherers. Recent ethnographic, archaeological and genetic studies have provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 143 publications
(203 reference statements)
1
52
0
Order By: Relevance
“…Further work, however, has provided evidence that this is an over-simplification, because the strongest effects occur in population networks composed of sub-groups in separate neighbourhoods, while being partially or intermittently connected [ 98 , 99 , 108 110 ]. As noted in the section above, these findings concur well with those arising from recent studies among real-world HG social networks [ 93 , 94 , 96 , 97 , 100 ].…”
Section: Collective Knowledge and Cumulative Culture In Humanssupporting
confidence: 91%
See 3 more Smart Citations
“…Further work, however, has provided evidence that this is an over-simplification, because the strongest effects occur in population networks composed of sub-groups in separate neighbourhoods, while being partially or intermittently connected [ 98 , 99 , 108 110 ]. As noted in the section above, these findings concur well with those arising from recent studies among real-world HG social networks [ 93 , 94 , 96 , 97 , 100 ].…”
Section: Collective Knowledge and Cumulative Culture In Humanssupporting
confidence: 91%
“…The artefacts provide us with a progressively more detailed record of the evolution of human material culture, but limited inferences can be drawn about social matters such as collective action and knowledge. By contrast, rich data on the latter come from the study of present-day peoples dependent on the hunting and gathering (HG) ways of life that the archaeological material tells us characterized millennia of our species' recent history [ 93 ]. However, the cultures of these communities tend to be very stable, revealing little of evolutionary change, whereas change permeates the archaeological record of the last few million years.…”
Section: Collective Knowledge and Cumulative Culture In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the first study demonstrated how a shared innovation may arise through two sequential manifestations of collective phenomena: first, the combination of different chimpanzees' exploratory actions, coupled with observational learning, to create a novel technology (LBT usage); and second, social learning by others from this, so collective knowledge of it becomes shared across a group [ 27 ]. We can summarize this in the conclusion that collective knowledge can be both an important cause and a consequence in the emergence of cumulative culture as in the human case [ 75 ]. As we noted above, this conclusion is based on a serendipitous set of observations, contrasting with many other reports of a lack of cumulative cultural change in chimpanzee social learning experiments [ 43 , 45 , 47 ].…”
Section: Concluding Discussionmentioning
confidence: 99%